How boxers decide to punch a target: Emergent behaviour in nonlinear dynamical movement systems - Hristovski, R.; Davids, K.; Araujo, D.; Button, C. (Journal of Sports Science & Medicine, 2006)
Previous research has shown how dynamical systems theory provides a relevant framework for investigating decision-making behavior in sport. The aim of this study was to adopt concepts and tools from nonlinear dynamics in examining effects of boxer-target distance and perceived punching efficiency on emergent decision-making during a typical practice task in boxing. Results revealed the existence of critical values of scaled distances between boxers and targets for first time appearance and disappearance of a diverse range of boxing actions including jabs, hooks and uppercuts. Reasons for the diversity of actions were twofold: i) abrupt (qualitative) changes in the number of the possible punches, i.e. motor solutions to the hitting task; and ii), fine modification of the probabilities of selecting specific striking patterns. Boxers were able to exploit the emerging perception of strikeability, leading to a changing diversity of selected actions and a cascade of abrupt changes in the perceptual-motor work space of the task. Perceived efficiency of a punching action by the participants also changed as a function of the scaled distance to a target and was correlated with the probability of occurrence of specific boxing actions. Accordingly, scaled distance-dependent perceived efficiency seems an important perceptual constraint in the training task of punching a heavy bag in boxers.